ASSESS THE AWARENESS ON ILL-EFFECT OF ELECTRONIC WASTE ON HEALTH AMONG GENERAL POPULATION OF SELECTED URBAN COMMUNITY - Julie Vanlalsawmi, Pratibha Wankhede ,Dr. Manoj Patil (International Journal of Modern Agriculture, 2020)
Introduction: The increase use of these electronics equipment leads to increase in the amount of electronic waste. This study is planned to assess the awareness on ill effect of electronic waste among general population of selected urban community and to associate the awareness on ill effect of electronic waste on health among selected urban community with a selected demographic variable. Methodology – It will be a quantitative research approach and it will be conducted among 100 selected sample of community urban area of Aarvi Naka. Self-structured questionnaire will be used to collect data. Expected Results: Gaps in related knowledge are expected to be more. The conclusion will be drawn from the results..